Visible Light Induced Photodegradation of Methylene Blue in Sodium Doped Bismuth Barium Ferrite Nanoparticle Synthesized by Sol-gel Method - Abdurrashid Haruna; Ibrahim Abdulkadir; Suleiman Ola Idris (Hamadan University of Medical Sciences, 2018)
Perovskite-like BiFeO3 nanoparticles doped with barium and sodium ions were synthesized via the citric acid route by the sol-gel method. The as-prepared Bi0.65Na0.2Ba0.15FeO3 nanopowders were divided into three equal portions and separately annealed at various annealing temperatures of 600, 700 and 800°C. The powders were characterized using X-ray diffraction (XRD) and crystallized with a rhombohedral R3c space group. Scanning electron microscopy was used to determine the morphology of the crystal and Fourier transform infrared spectroscopy was conducted at room temperature to determine the phase purity and the B-site formation in the perovskite structure. The UV-vis diffuse reflectance spectroscopy of all the materials was investigated, showing strong photoabsorption (λ > 420 nm). The doping effect of BiFeO3 enhanced photocatalytic activity while it significantly reduced the energy bandgap to 2.05 eV (for BNBFO at 800°C) which showed strong visible light absorption. The photocatalytic activity of Bi0.65Na0.2Ba0.15FeO3 nanomaterials was tested by monitoring the degradation rate of methylene blue dye pollutant under visible light irradiation in aqueous solution. All powders showed photoactivity after 2 hours of visible light irradiation. The annealing temperature greatly affected the methylene blue degradation, showing the efficiencies of 57, 67 and 75 % for BNBFO at 600, 700 and 800°C, respectively. Kinetic studies were carried out and the rate constants of 6.70 x 10-3, 8.90 x 10-3 and 1.05 x 10-2 min-1 were obtained for powders annealed at 600, 700 and 800°C, respectively. The photocatalytic mechanism of the degradation process was proposed in this study.